Shift in Cultivation Forms and importance in Sustainable Development Strategy - R. Tilfah, Habeeb (Journal of College of Education, 2021)
To achieve long-term sustainable development, whether in rural or urban areas, one should examine the geomorphology of each environment. Perhaps the most prominent features of the rural setting are cultivation, recreation areas, and utility facilities. This study is concerned with cultivation forms across Iraq, with a special emphasis on Wasit province, being the leading provider of various crops, the top of which are grains. Aziziya township was selected as a test model to apply development criteria and prospective steps, where wheat topped other crops. The wheat cultivation in Aziziya ranked first, compared with other crops in the lands cultivated, about 65%, or about 10.06% of the total cultivated lands across Wasit. Wasit has 947658 acres cultivated, the largest in 2018, which makes it the top crop provider across Iraq. The study maintains that a shift in cultivation forms, throughout 2015-2018, is attributed to a change in water resources by 71.6%. This shift is shown by the identification factor (R2). As for the spatial relationship strength between cultivation forms and identification factors, shown in simple correlation factor (R), this is a potential and centrifugal connection, amounting to 84.6%. The study, drawing on the classification of cultivation forms and relevancy to water resource change, designates four key sustainable development areas in the data sampled for the test, based on a quartile data classification. These areas are; 1.Safe strategic development area 2.Flexible sustainable development area 3.Changing development area 4.Restricted development area These areas reflect how lands respond to geographic variables, which control any rural cultivation form, as in water resources required to achieve a well-established sustainable development in the future.